(untitled) (Journal of Universal Excellence, 2026)
Research question (RQ): How to educate competent individuals who will be successful in marketing in the field of floristics? Which competences are important for a florist to independently lead a project? Which experiences are the most important in the process of education? Purpose: The goal of our research was to analyse a group of successful candidates which walked different education paths but with a common goal – become successful in the field of floristics. Method: We designed a multiparameter decision-making model using a computer programme DEXI, in which we assigned different weight of importance to individual parameters regarding the effect the have on participants. We assigned different weight to individual parameters based on 17-year experiences in floristics. Weighting was determined after consulting international professionals from Sweden, Finland, Italy, Slovakia, Croatia and Slovenia who are cooperating in an international project in order to produce an international school textbook of floristics. Results: The model showed the biggest influence of education, during which the candidates passed FlorCert exam. Cooperating in various florist projects also showed to be of great importance. Candidates with this experiences are successful in marketing, independent and employable. The independently lead small project teams, to which the informally pass their knowledge. Organization: This research confirmed the correctness of the decision to affiliate Floweracademy.si with FlorCert consortium, to further continue education on an international scale. It is also important to track novelties in floristics to enable the placement of candidates in international projects. Society: This way the society gains responsible, competent florists, who offer quality services. Being members of FlorCert they are following the sustainable development of floristics and are socially responsible with the use of various materials.